Case Report: Pancreaticopleural fistula with an atypical tract in a child with bulging chest - Shang, Zi Yin; Hong, Chun; Liu, Cui Fen (Frontiers in Pediatrics, 2023)
Pancreaticopleural fistula (PPF) is a rare but serious complication caused by pancreatic lesions that presents primarily with respiratory tract symptoms and pleural effusion. We report a paediatric case of PPF without any respiratory symptoms throughout the course of the disease, including cough or shortness of breath, with only a bulging chest as the first symptom. Imaging revealed a large left pleural effusion and Magnetic Resonance Cholangiopancreatography (MRCP) revealed a fistula formed between the pancreatic tail and the pleural cavity, which penetrated the diaphragm and opened in the central tendon of the diaphragm. The patient eventually underwent resection of the pancreatic tail lesion and repair of the diaphragmatic fistula and recovered soon thereafter.